Nano-cellulose biopolymer based nano-biofilm biomaterial using plant biomass: An innovative plant biomaterial dataset - Sharif Hossain, A.B.M.; Uddin, Musamma M.; Fawzi, Mohammad; Veettil, Vajid N. (Elsevier, 2018)
The nano-cellulose derived nano-biofilm keeps a magnificent role in medical, biomedical, bioengineering and pharmaceutical industries. Plant biomaterial is naturally organic and biodegradable. This study has been highlighted as one of the strategy introducing biomass based nano-bioplastic (nanobiofilm) to solve dependency on petroleum and environment pollution because of non-degradable plastic. The data study was carried out to investigate the nano-biopolymer (nanocellulose) based nano-biofilm data from corn leaf biomass coming after bioprocess technology without chemicals. Corn leaf biomass was used to produce biodegradable nano-bioplastic for medical and biomedical and other industrial uses. Data on water absorption, odor, pH, cellulose content, shape and firmness, color coating and tensile strength test have been exhibited under standardization of ASTM (American standard for testing and materials). Moreover, the chemical elements of nanobiofilm like K+, CO3 −−, Cl−, Na+ showed standard data using the EN (166).